2018
DOI: 10.5114/amscd.2018.81070
|View full text |Cite
|
Sign up to set email alerts
|

The role of matrix metalloproteinases in cancer progression, in particular metastasis

Abstract: Cancer is a major global health concern, and is one of the leading causes of mortality in many developed countries including Australia. Most of the morbidity and mortality associated with cancer can be linked to the process of metastasis, whereby malignant cancerous cells move from their primary site to establish secondary tumours at a distant location. The capacity of cells to migrate through a tissue depends on their ability to degrade the extracellular matrix. Matrix metalloproteinases are the main protease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 245 publications
(342 reference statements)
2
1
0
Order By: Relevance
“…[24][25][26] It is reported that rate of metastasis of tumor cells is directly related with the expression of MMPs in the cells. 24,27,28 In the current study, tretinoin treatment led to a prominent reduction in MMP-2 and MMP-9 expression in HT-3 cervical cancer cells in dose-dependent manner. Increase in concentration of tretinoin caused more prominent decease in expression of MMP-2 and MMP-9 proteins in HT-3 cells.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…[24][25][26] It is reported that rate of metastasis of tumor cells is directly related with the expression of MMPs in the cells. 24,27,28 In the current study, tretinoin treatment led to a prominent reduction in MMP-2 and MMP-9 expression in HT-3 cervical cancer cells in dose-dependent manner. Increase in concentration of tretinoin caused more prominent decease in expression of MMP-2 and MMP-9 proteins in HT-3 cells.…”
Section: Discussionsupporting
confidence: 55%
“…Metastasis of the tumor cells through the extracellular matrix and basement membrane is associated with the production of MMP 24–26 . It is reported that rate of metastasis of tumor cells is directly related with the expression of MMPs in the cells 24,27,28 . In the current study, tretinoin treatment led to a prominent reduction in MMP‐2 and MMP‐9 expression in HT‐3 cervical cancer cells in dose‐dependent manner.…”
Section: Discussionsupporting
confidence: 50%
“…By contrast, downregulation of MSK1 caused completely opposite consequences compared to the control cells (Figures 3 A and B). Previous studies have shown that matrix metalloproteinase-2 (MMP2) and MMP9 promoted tumor invasion and metastasis by degrading extracellular matrices [31,32]; thus the protein expression of MMP2 and MMP9 were assessed. The results suggested that MMP2 and MMP9 expression levels were increased by overexpression of MSK1 and decreased by MSK1 knockdown in OCM-1A and MUM-2C cell lines (Figure 3 C).…”
Section: Msk1 Promotes Uveal Melanoma Cell Metastasismentioning
confidence: 99%